Exacerbación aguda de la enfermedad pulmonar obstructiva crónica por infección en una paciente con estadio Gold IV - Yaulema Riss, Aymaru (2017)
Chronic obstructive pulmonary disease is characterized by obstruction of the respiratory flow, sometimes not completely reversible; generally, the obstruction follows a progressive evolution and is associated with a pathological pulmonary inflammatory reaction to toxic gases or particles. The acute exacerbation subsequent to an infection is a complication, seriousness that can compromise the life of the patient. The case report concerns a 68-year-old patient with diagnosed chronic obstructive pulmonary disease (COPD), complicated by an acute bacterial infection that warrants admission to intensive care (ICU) and the use of complex therapy. The text details diagnostic, therapeutic and evolution aspects; it is complemented with an analysis of current therapies recommended by international guidelines, debates on new therapeutic schemes and insists on the abandonment of smoking habit in the face of COPD